Reproductive Toxicity of Ethanolic Extract of Lecaniodiscus cupanioides on Male Albino Mice - Adeola Michael Oloyede *; Chidalu Christabel Anyika; Bodunrin Ottu (Lorestan University of Medical Sciences, 2020)
Background and Aim: Lecaniodiscus cupanioides is one of the numerous plants therapeutically used in  Southwestern Nigeria for controlling and curing several health complications. In this study, the in vivo effects of the ethanolic extract of L. cupanioides on sperm morphology of albino mice were investigated. Materials and Methods: Fifteen mice (18.2g to 24.8g) were divided into 3 groups of 5 mice. The treatment groups were orally administered 100 and 400mg/kg of the extract, and the control group received distilled water for 49 days. At the expiration of exposure, the mice were sacrificed by jugular puncture. Epididymis and testes were harvested for sperm cytological analysis and testes histology. Results: Fourteen types of sperm morphological abnormalities observed included: no hook, head with double tails, knobbed hook, amorphous head, bent hook, hook at wrong angle, tail folded over head, pin head, banana-shaped head, tail with no head (prominent), tail with double heads, head with triple tails, wrong tail attachment and head with no tail. Incidence was not significantly different from the control. Furthermore, no correlation between the dose level of the administered drug and incidence of abnormal sperms was observed. Hence, various abnormalities might probably be adduced to natural mistakes during differentiation in spermiogenesis, chromosomal aberration during packaging of genetic material in sperm head, occurrence of small deletions and point mutation during spermatogenesis. Histology of the testes did not show any malformation or alteration, which implies a highly conserved histoachitecture. Conclusion: This suggests that the extract might be devoid of any toxic effect on the male reproductive organs and sperms at the doses evaluated within the exposure period